Preschool Education Students in Higher Vocational Colleges under the Background of "Healthy China" - Lu, Jinghui (Journal of Theory and Practice of Contemporary Education, 2024)
The health of young children is the key to achieving a "Healthy China". As "quasi teachers" of preschool education in vocational colleges, their scientific care level directly affects the health level of young children. This paper expounds the connotation of scientific literacy, analyzes the importance of improving the scientific literacy of preschool education students, and gives some thoughts on improving the scientific literacy of preschool education students in higher vocational colleges based on teaching practice.